Response of silicon nitride ceramics subject to laser shock treatment - Shukla, Pratik; Shen, X.; Allott, Ric; Ertel, Klaus; Robertson, S.; Crookes, R.; Wu, H.; Zammit, A.; Swanson, P.; Fitzpatrick, M.E. (Ceramics international, 2021)
A comprehensive and novel investigation on multiple-layer, square-beam laser shock treatment (“laser peening”) of Si3N4 ceramics is reported in this work. Surface topography, hardness, fracture toughness (KIc), residual stresses, and microstructural changes were investigated. The evaluation of fracture toughness via the Vickers hardness indentation method revealed a reduction in crack lengths produced by the indenter after laser shock treatment (LST). Upon appropriate calculation, this revealed an increase in KIC of 60%. This being attributed to a near-surface (50 μm depth) compressive residual stress measured at −289 MPa. Multiple layer LST also induced beneficial residual stresses to a maximum measured depth of 512 μm. Oxidation was evident, only on the top surface of the ceramic, post LST (<5 μm depth) and was postulated to be due to hydrolyzation. The surface enhancement in KIC and flaw-size reduction was assigned to an elemental change on the surface, whereby, Si3N4 was transformed to SiO2, particularly, with multiple layers of LST. Compressive residual stresses measured in the sub-surface were attributed to mechanical effects (below sub-surface elastic constraint) and corresponding shock-wave response of the Si3N4. This work has led to a new mechanistic understanding regarding the response of Si3N4 ceramics subject to the LST deployed in this resesrch. The findings are significant because inducing deep compressive residual stresses and corresponding enhancement in surface KIC are important for the enhanced durability in many applications of this ceramic, including cutting tools, hip and knee implants, dental replacements, bullet-proof vests and rocket nozzles in automotive, aerospace, space and biomedical industries. [Display omitted]